ЯЗЫКОВАЯ ЭКСПЛИКАЦИЯ КОНЦЕПТА РЕЛЬЕФ ЗЕМЛИ В РУССКОМ ЯЗЫКЕ - Chomko, Jolanta (Acta Neophilologica, 2014)
This article deals with the reconstruction of the linguistic picture of the world. The analysis concerns one of the forms of explanation of the concept of “shape of surface” – i.e., lexemes verbalizing this concept. The richness of linguistic resources which verbalize the concept of “shape of surface” testifies to its importance to Russian mentality. Characteristics of the shape of surface, documented by linguistic data, are: “place,” “shape,” “size,” “way of formation,” “presence of vegetation,” “kind of mineral of the hill,” “existence of water in recess,” “existence of the crater,” “ranges.”